Cumulative air pollution indicators highlight unique patterns of injustice in urban Canada. (15th December 2020) - Giang, Amanda; Castellani, Kaitlin
Abstract: Disparities in air pollution exposure are a form of distributional environmental injustice that has been documented in many jurisdictions around the world. In Canada, although there is a growing literature characterizing exposure inequalities, an important gap is research that captures the cumulative impact of the multiple air pollutants to which communities are exposed. Here, we present a screening-level analysis of inequalities in single pollutant and cumulative air pollution burdens in three major cities in Canada: Toronto, Montreal, and Vancouver. We construct three cumulative hazard indices (CHIs), using previously published national datasets for PM2.5, NO2, SO2, and O3 concentrations for illustrative year 2012. We describe the ways in which patterns of inequality differ between pollutants, between ways of calculating cumulative burden, and between cities. Different methods of constructing CHIs can yield different understandings of the spatial distribution of pollution, and in turn, inequality. We find the largest spatial variations for a CHI based on whether each pollutant exceeds an external benchmark (here, air quality guidelines), which translates into the largest calculated disparities in cumulative air pollution burdens for marginalized groups. We observe distinct patterns of inequality between the cities, in terms of which marginalized groups consistently experience higher cumulative air pollution burdens (Vancouver: Indigenous residents, Montreal: immigrant residents, Toronto: low-income residents). Results also highlight the importance of using a suite of socio-demographic indicators as patterns can differ between individual racialized/ethnic groups, and between different measures of socio-economic status. This work illustrates how a range of cumulative hazard screening indicators could be used in a policy context in Canada and elsewhere, while highlighting some of the methodological complexities in how environmental and social risks are characterized and combined. Given these complexities, we suggest that community input should inform the design of environmental justice indicators, as an important component of procedural justice.